Study design and subject baseline characteristics in the ADVANCE Study: effects of cinacalcet on vascular calcification in haemodialysis patients - Floege, Jürgen; Raggi, Paolo; Block, Geoffrey A.; Torres, Pablo Urena; Csiky, Botond; Naso, Agostino; Nossuli, Kaldin; Moustafa, Moustafa; Goodman, William G.; Lopez, Nicole; Downey, Gerry; Dehmel, Bastian; et al. (Nephrology, dialysis, transplantation, 2010)
Background. The ADVANCE (A Randomized Study to Evaluate the Effects of Cinacalcet plus Low-Dose Vitamin D on Vascular Calcification in Subjects with Chronic Kidney Disease Receiving Haemodialysis) Study objective is to assess the effect of cinacalcet plus low-dose active vitamin D versus flexible dosing of active vitamin D on progression of coronary artery calcification (CAC) in haemodialysis patients. We report the ADVANCE Study design and baseline subject characteristics. Methods. ADVANCE is a multinational, multicentre, randomized, open-label study. Adult haemodialysis patients with moderate to severe secondary hyperparathyroidism (intact parathyroid hormone [iPTH] >300 pg/mL or bio-intact PTH >160 pg/mL) and baseline CAC score ≥30 were stratified by CAC score (≥30–399, ≥400–999, ≥1000) and randomized in a 1:1 ratio to cinacalcet (30–180 mg/day) plus low-dose active vitamin D (cinacalcet group) or flexible dosing of active vitamin D alone (control). The study had three phases: screening, 20-week dose titration and 32-week follow-up. CAC scores obtained by cardiac computed tomography were determined at screening and weeks 28 and 52. The primary end point was percentage change in CAC score from baseline to Week 52. Results. Subjects (n = 360) were randomized to cinacalcet or control. Mean age was 61.5 years, 43% were women, and median dialysis vintage was 36.7 months (range, 2.7–351.5 months). The baseline geometric mean CAC score by the Agatston method was 548.7 (95% confidence interval, 480.5–626.6). Baseline CAC score was independently associated with age, sex, dialysis vintage, diabetes and iPTH. Subjects also had extensive aortic and valvular calcification at baseline. Conclusions. Subjects enrolled in ADVANCE have extensive CAC at baseline. The ADVANCE Study should help determine whether cinacalcet attenuates progression of vascular calcification.